MENINGKATKAN KEMAMPUAN PEMAHAMAN BENTUK GEOMETRI DASAR (2D) PADA SISWA KELAS 2 SD MENGGUNAKAN MEDIA PANKUBANGTAR (PAPAN BERPAKU BANGUN DATAR) - Dwi Puji Artika Zebua, Hotma Siregar; Yusni Khairul Amri, Nurasiah Hasibuan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Classroom Action Research conducted in April 2025 in class 2A SDN 064974 Medan Tembung, academic year 2024/2025 with a total of 23 students aimed at improving geometric knowledge of two-dimensional shapes using PANKUBANGTAR media (Panjang Paku Bangun Datar). By employing a realistic approach through Culturally Responsive Teaching (CRT) and implementing a Problem Based Learning (PBL) model, the students' learning outcomes improved from an initial average score of 66.7 (cycle I) with a completeness 56.5% to 78.3% with an average score of 72.8 (cycle II), ultimately achieving 100% completeness with an average score of 86.5 (cycle III). The use of innovative media greatly helps make learning interactive and student-centered. Each improvement from each cycle leads to perfect learning outcomes in accordance with the expected learning objectives